The Teachers of the Third Primary Grade Satisfaction Degree with the Content of “The Learning Loss” Book for the Arabic Language Subject - Abu Suileek, Aisha Bader; Abu Qtaish, Huda Yahya (Dirasat: Educational Sciences, 2023)
Objectives: The study aims to reveal the degree of satisfaction of teachers of the third grade with the content of “The learning Loss” book for the Arabic language subject, and to determine whether gender, experience, and educational institution influence teacher satisfaction. Methods: A sample of 254 teachers from the Ministry of Education of the governorates of Oman and Zarqa for the academic year 2021/2022 participated in this study, using the survey curriculum. A (20) paragraph questionnaire was designed to measure the level of satisfaction of third-grade teachers with the content of the Book of Loss of Education in Arabic. Arithmetic means were judged as follows: from (1.00-1.99) low, (2.00-2.99) medium, and (3.00-4.00) high. Results: The results showed that teachers of the third primary grade were moderately satisfied with the content of "The learning Loss" book for the Arabic language, the arithmetic mean was (2.92±0.653). The results also indicated statistically significant differences in satisfaction by gender in favor of the males, while there were no statistically significant differences in satisfaction by experience or educational institution. Conclusions: After evaluating the results, teachers of the third primary grade expressed their dissatisfaction with some of the contents of the book “The learning loss of Arabic Language” as its content conflicted with the number of classes prescribed. Thus, the study recommended increasing the number of classes assigned to it.